INFLUENCE OF ORGANIZATIONAL CULTURE, EDUCATION, AND TRAINING ON EMPLOYEE PERFORMANCE WITH MOTIVATION AS VARIABLE INTERVENTION - Agus Dwi Atmoko (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to examine the influence of the organizational culture of education and training on employee performance with motivation as a study intervention variable at the Sawunggalih Aji Polytechnic, of Purworejo’s District. Data were analyzed using research instrument analysis which includes an examination of validity using analysis correlation product-moment, examination of reliability using Cronbach’s alpha technique, examine of hypothesis using Rule of Abralisis technique. The result of this research shows that: 1) there are positive and significant influences of the culture of the organization to motivate the staff, 2) there are positive and significant influences on the education and training to motivate the staff, 3) there are positive and significant influences of cultural of the organization to the performance of the staff, 4) there are positive and significant influences to the education and training to the performance of the staff, 4) there is negative motivation to the performance of the staff. This study uses linear regression analysis with the use of intervening variables, so the data analysis of this study uses intervening regression analysis/path regression. The variables studied are in this study to examine the strength of the relationship and the magnitude of the influence of organizational culture, education, and training on employee performance and the indirect effect of organizational culture and education and training through motivation on performance. The research was conducted with locations and employees at the Sawunggalih Aji Polytechnic. Conditions at the Sawunggalih Aji Polytechnic currently still have limitations with various problems. The limitations experienced include financial capacity, limited access to information and technology. Therefore, literacy of Organizational Culture, Education, and Training Motivation to improve performance. Several studies have been conducted to prove that literacy in Organizational Culture, EducationTraining, and Motivation has an impact on increasing employee performance. This research offers interesting recommendations related to organizational policies to increase work engagement and its dimensions. Based on the findings of this study, the direct effect of education and training, as well as organizational culture on performance is more dominant than the indirect effect through motivation.